2022
DOI: 10.1186/s12915-022-01351-x
|View full text |Cite
|
Sign up to set email alerts
|

Light regulates the degradation of the regulatory protein VE-1 in the fungus Neurospora crassa

Abstract: Background Fungi use light as an environmental signal to regulate developmental transitions that are key aspects of their biological cycles and that are also relevant for their dispersal and infectivity as plant or animal pathogens. In addition, light regulates the accumulation of photoprotective pigments, like carotenoids, and other secondary metabolites. Most fungal light responses occur after changes in gene transcription and we describe here a novel effect of light in the regulation of degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…2E ), but the accumulation of VE-1 in nuclear fractions was mostly observed after the induction of conidiation in the dark ( Fig. 2D ), as we previously reported in light-exposed cultures ( 29 ). Our observations on the abundances and the nuclear localization of VE-1 and VE-2 suggest that VE-1 is the limiting component of the velvet complex and that the regulation of its abundance and subcellular localization plays a key role in the activity of the velvet complex during asexual development.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…2E ), but the accumulation of VE-1 in nuclear fractions was mostly observed after the induction of conidiation in the dark ( Fig. 2D ), as we previously reported in light-exposed cultures ( 29 ). Our observations on the abundances and the nuclear localization of VE-1 and VE-2 suggest that VE-1 is the limiting component of the velvet complex and that the regulation of its abundance and subcellular localization plays a key role in the activity of the velvet complex during asexual development.…”
Section: Resultssupporting
confidence: 85%
“…Initial studies have shown that the absence of VE-1 led to a light-dependent shortening of aerial tissue, a mixture of aerial hyphae and developing macroconidia, that required the activity of the photoreceptor WC-1 ( 29 ). This observation, together with the proposed role of the velvet complex in the regulation of asexual development in N. crassa ( 28 ), prompted us to further characterize the roles of VE-1 and VE-2 in the growth of aerial tissue, the amounts of conidia in single and double deletion mutants, and their possible regulation by light.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations